Juridical Analysis of Integrated Electronic Responsibility Services based on Agricultural & Spatial Land Regulation - Ferika Rahmatul Zulfa; Anis Mashdurohatun (Sultan Agung Notary Law Review, 2021)
HT-el service is a form of service provision from the Ministry of ATR / BPN in facilitating services to the community by taking advantage of developments in information technology. Implementation of Permen No. 9/2019 concerning electronic HT still depends on the readiness of each land office in implementing an electronic system. There are many advantages that are obtained in the online registration feature, but there are also many disadvantages in it. One of the advantages obtained in this online registration is that it can save time for users of the land bureaucracy, of course the main hope is that the effectiveness and efficiency of the bureaucracy can actually be achieved legal system construction and constraints. This study uses an empirical juridical approach. This research analyzes the problems that have been formulated by combining primary, secondary and tertiary legal materials.